Signal peptide of HIV-1 envelope modulates glycosylation impacting exposure of V1V2 and other epitopes. - Chitra Upadhyay; Roya Feyznezhad; Liwei Cao; Kun-Wei Chan; Kevin Liu; Weiming Yang; Hui Zhang; Jason Yolitz; James Arthos; Arthur Nadas; Xiang-Peng Kong; Susan Zolla-Pazner; et al. (PLoS Pathogens, 2020)
HIV-1 envelope (Env) is a trimer of gp120-gp41 heterodimers, synthesized from a precursor gp160 that contains an ER-targeting signal peptide (SP) at its amino-terminus. Each trimer is swathed by ~90 N-linked glycans, comprising complex-type and oligomannose-type glycans, which play an important role in determining virus sensitivity to neutralizing antibodies. We previously examined the effects of single point SP mutations on Env properties and functions. Here, we aimed to understand the impact of the SP diversity on glycosylation of virus-derived Env and virus neutralization by swapping SPs. Analyses of site-specific glycans revealed that SP swapping altered Env glycan content and occupancy on multiple N-linked glycosites, including conserved N156 and N160 glycans in the V1V2 region at the Env trimer apex and N88 at the trimer base. Virus neutralization was also affected, especially by antibodies against V1V2, V3, and gp41. Likewise, SP swaps affected the recognition of soluble and cell-associated Env by antibodies targeting distinct V1V2 configurations, V3 crown, and gp41 epitopes. These data highlight the contribution of SP sequence diversity in shaping the Env glycan content and its impact on the configuration and accessibility of V1V2 and other Env epitopes.